A superior extracellular matrix binding motif to enhance the regenerative activity and safety of therapeutic proteins - Yasmin K. Alshoubaki; Yen-Zhen Lu; Julien M. D. Legrand; Rezvan Karami; Mathilde Fossat; Ekaterina Salimova; Ziad Julier; Mikaël M. Martino (npj Regenerative Medicine, 2023)
Abstract Among therapeutic proteins, cytokines and growth factors have great potential for regenerative medicine applications. However, these molecules have encountered limited clinical success due to low effectiveness and major safety concerns, highlighting the need to develop better approaches that increase efficacy and safety. Promising approaches leverage how the extracellular matrix (ECM) controls the activity of these molecules during tissue healing. Using a protein motif screening strategy, we discovered that amphiregulin possesses an exceptionally strong binding motif for ECM components. We used this motif to confer the pro-regenerative therapeutics platelet-derived growth factor-BB (PDGF-BB) and interleukin-1 receptor antagonist (IL-1Ra) a very high affinity to the ECM. In mouse models, the approach considerably extended tissue retention of the engineered therapeutics and reduced leakage in the circulation. Prolonged retention and minimal systemic diffusion of engineered PDGF-BB abolished the tumour growth-promoting adverse effect that was observed with wild-type PDGF-BB. Moreover, engineered PDGF-BB was substantially more effective at promoting diabetic wound healing and regeneration after volumetric muscle loss, compared to wild-type PDGF-BB. Finally, while local or systemic delivery of wild-type IL-1Ra showed minor effects, intramyocardial delivery of engineered IL-1Ra enhanced cardiac repair after myocardial infarction by limiting cardiomyocyte death and fibrosis. This engineering strategy highlights the key importance of exploiting interactions between ECM and therapeutic proteins for developing effective and safer regenerative therapies.